2007
DOI: 10.1007/s00383-007-1940-8
|View full text |Cite
|
Sign up to set email alerts
|

Lung resections in children for congenital and acquired lesions

Abstract: We reviewed a single-center experience of pediatric lung resections for various congenital and acquired benign lung conditions. Thirty-five children underwent lung resections between 1998 and 2006, their age ranging from 8 days to 12 years (mean 3 years), with a male:female ratio of 4:1. Twelve patients were neonates. Antenatal diagnosis was available in only one patient. The presenting symptoms were respiratory distress and respiratory tract infections. Imaging with chest X-ray with/without a CT scan picked u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 44 publications
0
27
1
2
Order By: Relevance
“…( 27 ) Some authors have reported that the symptoms are more intense when there is upper lobe involvement than when there is middle lobe involvement. ( 15 , 16 , 22 ) However, no such difference was found in our sample of patients. …”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…( 27 ) Some authors have reported that the symptoms are more intense when there is upper lobe involvement than when there is middle lobe involvement. ( 15 , 16 , 22 ) However, no such difference was found in our sample of patients. …”
Section: Discussioncontrasting
confidence: 74%
“…In both cases, the upper right and middle lobes in the right hemithorax were affected. This facilitated the surgical approach–as previously discussed by other authors( 15 , 22 )–which would have been more difficult had there been bilateral involvement. ( 27 ) Some authors have reported that the symptoms are more intense when there is upper lobe involvement than when there is middle lobe involvement.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Lobectomy is considered by some to be the procedure of choice for removal of CLMs [12][13][14][15] because complete resection of the diseased lobe leaves no possibility for residual disease [16,17] and the resultant risk of recurrent infection or malignant transformation [18][19][20][21][22]. In addition, some authors have speculated that the rate of postoperative air leak is less with lobectomy [3].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have concluded that surgical management is appropriate for all infants <2 months and for those over 2 months with severe respiratory distress, medistinal shift +/− lobar collapse on CXR or abnormal bronchoscopy findings 69. The appropriate surgical management is excision of the affected lobe 6 7. Conservative management involves serial clinical review with interval CXR’s to monitor progression.…”
Section: Discussionmentioning
confidence: 99%